TINGKAT AKURASI PENETAPAN NILAI JUAL OBJEK PAJAK BUMI TERHADAPNILAI PASAR DENGAN METODE ASSESSMENT SALES RATIO (STUDI KASUSPADAKECAMATAN MUARA SATU KOTA LHOKSEUMAWE) - Razif, Razif; Wati, Kasnah (Jurnal Akuntansi dan Keuangan, 2019)
The purpose of this study is to determine the level of accuracy of the determination of the object tax selling value (NJOP) of the earth to market value by the method of assessment sales ratio in Muara Satu subdistrict, Lhokseumawe City. The data used is quantitative data presented in the form of numbers of NJOP and Market Value. The used sample used is 30 data on purchasing and selling transactions. The analytical method used isdescriptive quantitative and data analysis using descriptive statistics, which used the asessment sales ratio test which includes measurement of central tendency, measurement of variability (COD and COV), and Study Ratio.based on the result of the analysis, it can be concluded whit that: a)Â  assessments sales ratio from each village is still not in accordance with the assessment ratio set by the local goverment, which is a minimum of 80%. b) the results of the measurement of the central level of assessment tendency in the NJOP determination in th Muara Satu subdistrict area are not in the interval standard international assosiation of assessing officers (IAAO). c) NJOP variability measurements in muara satu subdistrict have been set at a different level of assessment.